Предмет: Алгебра,
автор: katu141
(2x^+3х)^-7(2x^+3х)=10
Ответы
Автор ответа:
0
(2x^+3х)^-7(2x^+3х)=-10
2x^2+3x=t
t^2-7t+10=0
D=49-40=9
x12=(7+-3)/2=5 2
t=2
2x^2+3x=2
2x^2+3x-2=0
D=9+16=25
x12=(-3+-5)/4=-2 1/2
x1=-2
x2=-0.5
t=5
2x^2+3x=5
2x^2+3x-5=0
D=9+40=49
x34=(-3+-7)/4=1 -5/2
x3=1
x4=-2.5
----------------------------
2x^2+3x=t
t^2-7t+10=0
D=49-40=9
x12=(7+-3)/2=5 2
t=2
2x^2+3x=2
2x^2+3x-2=0
D=9+16=25
x12=(-3+-5)/4=-2 1/2
x1=-2
x2=-0.5
t=5
2x^2+3x=5
2x^2+3x-5=0
D=9+40=49
x34=(-3+-7)/4=1 -5/2
x3=1
x4=-2.5
----------------------------
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: lesnicevaleksandr59
Предмет: История,
автор: gunazamanzol
Предмет: Математика,
автор: lapysenok1982
Предмет: История,
автор: Ryabkova